2020
DOI: 10.1016/j.gore.2019.100520
|View full text |Cite
|
Sign up to set email alerts
|

HER2-positive metastatic cervical cancer responsive to first and second-line treatment: A case report

Abstract: HighlightsNext-generation sequencing can identify and offer new treatment options.Demonstration of the successful use of targeted therapy in metastatic cervical cancer.Patient sequentially responded to trastuzumab-pertuzumab followed by TDM-1.Duration of therapy has been four years and she continues to respond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…HER2 targeting drugs have demonstrated clinical efficacy against HER2-positive breast, gastroesophageal, and serous endometrial cancers, being the current therapeutic standards for these conditions and becoming investigational treatments in a continuously expanding set of solid tumors [ 13 17 ]. However, to our knowledge, no clinical trial assessing HER2 amplification/overexpression targeting agents in CC has been published to date, and the evidence of their successful use in this disease is limited to case reports [ 18 ]. The suitability of HER2 as an actionable target for clinical studies in CC would depend on HER2 positivity prevalence in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…HER2 targeting drugs have demonstrated clinical efficacy against HER2-positive breast, gastroesophageal, and serous endometrial cancers, being the current therapeutic standards for these conditions and becoming investigational treatments in a continuously expanding set of solid tumors [ 13 17 ]. However, to our knowledge, no clinical trial assessing HER2 amplification/overexpression targeting agents in CC has been published to date, and the evidence of their successful use in this disease is limited to case reports [ 18 ]. The suitability of HER2 as an actionable target for clinical studies in CC would depend on HER2 positivity prevalence in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Although HER2-targeting drugs (trastuzumab, pertuzumab, adotrastuzumab emtansine [TDM1], lapatinib) have improved survival in patients with HER2-positive lung, stomach, and cervical cancers, both inherent and developed resistance to HER2-targeting drugs still limit our effective management of this highly aggressive cancer subtype. [8][9][10] Therefore, effective HER2-targeted therapies for these patients are an unmet need, and efforts are being made to develop new anti-HER2 drugs.…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether these 23 candidate drugs had been previously associated with cervical cancer, we conducted an extensive literature search. We found that many of the drugs discovered had been used in or associated with cervical cancer ( 31 48 ) ( Table 1 ). Because studies in the literature generally do not include information on the HPV genotype of patients, we reviewed the drugs without considering HPV genotype to be on the safe side, and the drugs that had ever been associated with cervical cancer were not considered new in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of trastuzumab-pertuzumab, and the single-agent TDM-1, being effective in treatment of cervical cancer with HER2 amplification (48) interferon) is an unnatural synthetic interferon-alpha type 1 used to with chronic hepatitis C (57). Pimecrolimus was developed specifically for the treatment of inflammatory skin diseases (58).…”
Section: Discussionmentioning
confidence: 99%